Analysis of gender responsiveness of climate change response strategies in the Southern African development community (SADC) region - Nyahunda, Louis; Makhubele, Jabulani Calvin; Mabvurira, Vincent; Matlakala, Frans Koketso (Penerbit Universiti Kebangsaan Malaysia, 2019)
This paper sought to explore the gender responsiveness of climate change response strategies in the Southern African Development Community region. There is undisputable acknowledgement that all SADC countries are vulnerable to climate change impacts despite their low contribution to carbon gas emissions that cause climate change. Women are more encumbered by climate change effects than men due to poverty, low literacy levels, lack of adaptive capacity, ascribed gender roles and cultural discrimination patterns that promote patriarchal dominance. Arguably, the gendered differential vulnerability between women and men to climate change impacts is absent in most climate policy frameworks in SADC. The objective of the study was to establish the responsiveness of climate change policies to gender dimensions in the SADC region. The study followed a literature review as research methodology. Secondary data sources were purposively reviewed through the selection of relevant sources by the researchers which led to the identification of other sources guided by common themes and keywords. Data was analysed through the discourse analysis. The study established that most climate change response strategies in SADC demonstrated apt consideration of the roles of women in climate change mitigation and adaptation. It was concluded that women are recognised as vulnerable populations and their contribution in devising sustainable climate change solutions is overlooked at policy levels. The study recommended that climate change interventions can only be effective when they mainstream gender and acknowledge the contribution of women as agents of social change and most SADC countries are still lagging behind.